Uma análise da solvência das administrações públicas municipais das capitais brasileiras sob a ótica do serviço da dívida - Silva, Pedro José LIma (2017)
This study intends to investigate the financial solvency of the municipal public administrations of the Brazilian capitals using panel data methodology from 2008 to 2016. In particular, unit root tests are carried out in the ways idealized by Levin, Lin and Chu (2002) and Im, Pesaran and Shin (2003) on the public debt service of the Brazilian capitals, as well as regional breakdowns. With this, it is intended to contribute to the discussion on the subject with an innovative approach, because, instead of the contumative analysis on the consolidated debt, it is intended to maintain the scope in the public debt service, which includes amortization, charges, interest and monetary correction to the legally established threshold of 11.5% of the Municipal Net Revenue (RCL), pursuant to Resolution 43 of 2001 of the Federal Senate. The results suggest a global situation of unsustainability and only indications of a more austere behavior in the capitals of the Northeast region. These results are in line with the current systemic concern of managers faced with the serious fiscal crisis in the Brazilian public sector.